Challenges Faced by Teachers During Pandemic in Implementing Innovative Methods of Teaching - Siwach, Manoj Kumar; Vats, Richa (Journal of Commerce and Trade, 2022)
There has been a catastrophic effect on the general life of people during the period of infliction of COVID-19 pandemic. Almost everything came under its radar and that were hugely impacted. Same stands true for the teaching community. The most receptive sector in this regard has been the teaching sector, in which the automation technology has many newer methods and surprises which have influenced each and every phase from teaching methodology, to the mode and technique of teaching. Teachers in general faced several problems when they faced the pandemic of COVID-19. Multitude of them lost their jobs and who were left had to deal with the ordeal that war really hard for them given the less amount of knowledge and resources they had at their disposal. The foregoing shows that there were many changes that were adopted due to COVID-19, and which for sure have led to large scale problems for them. However, plethora of changes came into existence, which have been dealt in with new regime of teaching and this in fact introduced changes that are irreversible in every manner. Present paper provides a glimpse into the challenges faced by the teaching community and the methodologies they adopted to deal with those challenges. It suggests for the delineation of methods which were adopted by the teaching fraternity to deal with the challenges thrown by the advent of COVID-19.